Penanaman Pendidikan Karakter Peduli Lingkungan Melalui Program Adiwiyata Pada Siswa IPS Kelas IX Di SMPN 2 Kauman Tulungagung - Farzda Dwi Prahandani; Hendra Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
Instilling environmental care character education in students through the adiwiyata program is very important considering the development of science and technology which makes human behavior increasingly exploit natural resources and lose concern for the environment. Through the Adiwiyata program, environmental care character education is expected to generate and realize environmental awareness by introducing children to the importance of environmental conservation. Environmental preservation can be pursued, especially in schools, through the Adiwiyata program. One of the schools in Tulungagung Regency which has the adiwiyata title is SMPN 2 Kauman Tulungagung. This research is qualitative research with a qualitative descriptive research type. The data collection techniques used in this research are observation, interviews, documentation. The formulation of the problem in this research is related to activities in cultivating character education that cares about the environment, strategies for cultivating character education that cares about the environment, supporting and inhibiting factors for cultivating character education that cares about the environment. This research aims to: 1) find out the activities of instilling environmentally caring character education through the adiwiyata program in class IX social studies students at SMPN 2 Kauman Tulungnagung, 2) find out strategies for instilling environmentally caring character education through the adiwiyata program in class IX social studies students at SMPN 2 Kauman Tulungnagung, 3) determine the supporting and inhibiting factors for instilling environmentally caring character education through the adiwiyata program in class IX social studies students at SMPN 2 Kauman Tulungnagung. The results obtained from the research show that 1) in class VII, through socialization on waste recognition, socialization on waste selection, and socialization on waste banks, in class VIII there has begun to be a strengthening of the character of caring for the environment with discipline through class pickets, clean Fridays, not throwing away litter, keeping the classroom and yard clean, responsibility by being willing to accept punishment if you make a mistake, in class IX they have become role models for their younger classmates by giving examples of planting trees and caring for trees, 2) the strategy is that the school takes part in regular competitions, and schools make rules relating to adiwiyata, if anyone violates them they will be punished, 3) supporting factors such as example, teacher strictness, school regulations. Meanwhile, inhibiting factors include school internals, student habits, students' lack of awareness of obeying the rules..